A new model for the cantilever MEMS actuator in magnetorheological elastomer cored sandwich form considering the fringing field and Casimir effects. (15th April 2019) - Akhavan, Hossein; Ghadiri, Majid; Zajkani, Asghar
Highlights: The pull-in instability of a sandwich cantilever electrostatic MEMS actuator is investigated. The nonlinear governing equations have been solved with GDQM. The effects of Casimir force, the fringing field as well as, change in the thickness of the skin layers on pull-in parameters are studied. By applying various magnetic fields, the instability parameters significantly increase. Using sandwich structures with MRE, the pull-in voltage control is created for electrostatic MEMS actuator. Abstract: The study of the instability created by the pull-in voltage on electrostatic NEMS/MEMS devices have been studied by many researchers during the recent years. In the present study, considering the effects of Casimir force and fringing field, for the first time the pull-in instability of a Magnetorheological elastomer (MRE) sandwich cantilever MEMS actuator with conductive skins is investigated. The governing equations and the related boundary conditions are obtained through variational principle based on the Euler–Bernoulli beam theory. The obtained equations are solved using the generalized differential quadrature (GDQ) method. The MREs are smart materials which, by applying the magnetic field on them, their shear modulus can be changed and it's possible to control the stiffness of structures which use these materials as nuclei. By applying different magnetic fields, the results show a decrease in the deflection of the movable electrode and this causes the electrode to become unstable at higher voltages, in other words, as the magnetic field increases the pull-in voltage also increases. Using sandwich structures with MRE core to create cantilever MEMS actuator, the pull-in voltage control is created for this tool.